Estudo eletropalatográfico das seqüências /s s/ e /s S/ em português brasileiro (Revista de Estudos da Linguagem, 2007)
This paper analyses coarticulation process that occurs when onevoiceless alveolar fricative follows another alveolar voiceless fricativewith a word boundary between them and when one alveolar voicelessfricative follows a voiceless post-alveolar fricative with also a wordboundary between them. In order to do that, we utilized theelectropalatographic and spectrographic techniques. The resultsindicate that, in the context /s # s/, the sequence had the same acousticand electropalatographic characteristics as the voiceless alveolarfricative in initial syllable position, but the sequence /s # S/ presenteddifferent characteristics from both the voiceless alveolar fricativeand the voiceless post-alveolar fricatives.